Manual de la Ley de Propiedad y Cercado de Florida: Posesión Adversa - Michael T. Olexa; Joshua A. Cossey (EDIS)
Spanish version of the "Florida Fence and Property Law" handbook by Michael T. Olexa and Joshua A. Cossey. Published July 2007.